A COMPREHENSIVE ANALYSIS OF GLOBAL FOREIGN DIRECT INVESTMENT TRENDS: INSIGHTS INTO SECTORAL PATTERNS AND REGIONAL DISTRIBUTION - Murtozaev S. A. (American Journals, 2024)
This article provides a concise analysis of global foreign direct investment trends from 1990 to 2021. Drawing from authoritative reports, the study highlights the general changes in FDI flows over the period and examines their distribution by region and industry. The findings offer valuable insights into investment behavior, aiding policymakers and businesses in enhancing global investment strategies for sustainable economic growth.
Keywords: Foreign direct investment, global FDI flows, trends, developed countries, developing countries, M&A, greenfield investment, regions, industries, COVID-19, investment policy.